USING ROLE PLAY TO PORTRAIT THE LEARNING ENGAGEMENT OF THE ELEVENTH GRADERS IN SPEAKING CLASS (RETAIN, 2014)
USING ROLE PLAY TO PORTRAIT THE LEARNING ENGAGEMENT OF THE ELEVENTH GRADERS IN SPEAKING CLASS Irma Deviana English Department, Languages and Arts Faculty, State University of Surabaya dephy.sasoka@gmail.com Dra. Theresia Kumalarini, M.Pd. English Department, Languages and Arts Faculty, State University of Surabaya kumala_rini52@yahoo.co.id Abstrak Berlatih adalah kunci menjadi pembicara yang baik. Faktanya, beberapa siswa tidak berlatih untuk berbicara dalam bahasa inggris pada kegiatan berbicara. Akibatnya, mereka takut untuk mengekspresikan diri dan cenderung tidak berpartisipasi di kegiatan berbicara. Kearsley dan Shneiderman (1999) menyatakan bahwa siswa dengan penuh arti harus terikat dalam kegiatan belajar melalui interaksi dengan yang lain dan tugas yang berguna. Dengan mempertimbangkan hal ini, penelitian kualitatif ini bertujuan untuk mendeskripsikan bagaimana partisipasi siswa dalam kegiatan role play pada kemampuan berbicara. Subjek dari penelitian ini adalah siswa kelas sebelas di SMAN 13 Surabaya. Peneliti memilih 10 siswa sebagai sampel yang diperoleh dari informasi dari guru matapelajaran bahasa Inggris dan mewawancarai mereka kemudian menilainya. Setelah itu, mereka dibagi menjadi dua kategori, proficient dan less proficient. Peneliti mengumpulkan data melalui observation checklist. Kemudian, 10 siswa tersebut diwawancarai untuk memperkuat hasil observasi. Hasil dari penelitian ini menunjukkan bahwa siswa pada kedua kategori sama-sama berpartisipasi dalam kegiatan role play. Hasil dari wawancara menunjukkan bahwa hubungan antar teman menjadi kuat karena mereka bekerja sama selama role play. Oleh karena itu, peneliti menyarankan kepala guru pelajaran bahasa Inggris untuk menggunakan role play sebagai kegiatan berbicara untuk meningkatkan partisipasi siswa dan melatih siswa berbicara bahasa Inggris (Ladousse, 1987). Kata Kunci: Role Play, Partisipasi Siswa, Kegiatan Berbicara Abstract Keep practicing is the key to be a good speaker. In reality, some students do not practice to speak English in their speaking class. Consequently, they are afraid of speaking out and incline not to get involved in speaking class activity. Kearsley and Shneiderman (1999) stated that “students must be meaningfully engaged in learning activities through interaction with others and worthwhile tasks.” Considering this, this qualitative study aims to describe how the students’ engagement is in the implementation of Role Play in speaking class. The subject of this study was the eleventh graders of SMAN 13 Surabaya. The researcher selected ten students as the sample by describing the documentary information from the English teacher and interviewing the students then scoring them using speaking rubric. Afterwards, they were divided into two categories, i.e proficient and less proficient. In conducting the study, the researcher collected the data through observation checklist. Then, she interviewed the ten selected students to confirm the observation. The result showed that both proficient and less proficient students were all engaged in a role play activity. The result of the interview revealed that the relationship among friends was stronger as they worked in a team during the role play. Therefore, the researcher recommends that English teachers use role play as an activity in the speaking class to enhance the students’ engagement and train the students to say the right expression in the right place and at the right time (Ladousse, 1987). Keywords: Role Play, Students’ engagement, Speaking Class Activity INTRODUCTION A wise man ever said, “The more often you speak, the easier it becomes.” It simply means that practice often is the key to be a good speaker. In reality, there are some students especially EFL students who are still afraid of speaking English. Some of them worry to express what is in their mind or always keep thinking that people will not understand them when they are speaking. The reason is because they do not practice to speak English even in their oral class. This happens to students from lowest till highest levels. They get the same treatment where they just have little chance to speak. Besides, when the students get that little chance to speak, they incline not to get involved in speaking activity. Some of them are shy, not willing to share their ideas, and feel unprepared. This occurs due to lack of practice in speaking class. In addition, the condition of education in Indonesia is similar to that of China. Most students’ speaking skill is in the second-rate than other skills such as listening, reading and grammar. It results from getting high scores in the Higher Education Exam as the only purpose of the high school students. There is no speaking English test that is why speaking skill is often ignored. Besides, the students do not have more chance to speak because there are usually over 50 students per class (Jianing, 2007). Since this situation also occurs in Indonesia, the teachers should concern with this phenomenon. In reality, students do not have enough opportunity to practice speaking in class and the speaking skill itself is not taken any notice. It gives a big impact on the students. It makes them unwilling to participate in the activity, which is called the student’s engagement, when it really comes to speaking time. Dealing with the student’s engagement, the idea of engagement is that “students must be meaningfully engaged in learning activities through interaction with others and worthwhile tasks” (Kearsley & Shneiderman, 1999). It simply means that the students must actively get involved in the activity given. By doing so, the students will automatically communicate with other students. This shows that the students have a willing to study, in this case practicing speaking. Therefore, the point of the material will be easily understood by the students. On the contrary, if the students are unwilling to study, they will not have intention to participate in speaking activity. Some of them will just prefer to listen and keep silent or incline to be passive. That condition may prevent learners to have a good speaking performance. Dealing with it, role play is chosen to be a good practicing way in boosting student’s engagement in a speaking class. According to Brown cited by Huang (2008), "role-play minimally involves (a) giving a role to one or more members of a group and (b) assigning an objective or purpose that participants must accomplish." These simply mean that the students will get a role or character or position based on the topic given in a certain situation. They have to present it in the form of a dialogue or conversation in front of the class. This activity is done in order to enhance students’ ability in using English. Since it is conducted in a group, each student will get involved in the activity practicing their communicative skill. Besides, as students will have their own role in the activity, they can learn more how to interact with other students using English. Concerning the ideas above, the study of “Using Role Play to Portrait the Learning Engagement of The Eleventh Graders in Speaking Class” is conducted. It aims to know how the learning engagement of the tenth grader students is in speaking class through role playing activity. This study simply captures the engagement of students in such fun learning. Hopefully, this study can give big contribution to our education especially for speaking skill in English subject. METHODOLOGY To conduct this research, the writer selected the eleventh graders of SMA Negeri 13 Surabaya as the subject of this study. The researcher chose one class and selected ten students purposively as the samples. Then, they were divided into two categories, proficient and less proficient. In order to know which category each student belonged to, the researcher gave such kind of speaking test to them. The test was only about general conversation. Besides, the researcher also got the documentary information given by English teacher. This study used two instruments; observation checklist and interview. The researcher used observation checklist to observe directly the atmosphere of the class and student’s involvement during the teaching and learning process. Here is the form of the observation checklist: Aspects Rating Yes No 1. The students know the topic given The students respond to other student’s points/opinion in preparing role play The student support suggestions that may be counter to the majority opinion The students interact each other The students demonstrate the role playing performance consistently The students demonstrate active involvement in class The students demonstrate adequate preparation The students engage in the activity The students respond very thoughtfully to other student’s comments The students help other students to reduce anxiety in performing role play The students pay attention to the teacher The students are noisy and disruptive The students interact with teacher The students ask questions The situation of the class is crowded (Adapted from, Martha L. Maznevski, 1996) . The second instrument was the interview. This instrument aimed to obtain data about how the students’ feeling toward role playing. The students were asked about their feeling and the changes that affected them. Therefore, the interview could also be used to confirm the observation. In addition, the researcher listened to what they said by providing a recording so that all the students’ talk could be heard. The data from observing the class participation was described qualitatively. The researcher narrated the activities that both teacher and students did in the class during the teaching and learning process. The researcher analyzed the result of the interview given after the implementation of role playing. As the researcher used recorder, what the student say was listened repeatedly and transcribed. Then, the data was ready to be analyzed. As the transcript was made, the researcher organized all the data and analyzed it without changing the words or phrases that the students made. RESULTS Observation Here is the detail description of each student’s participation during the implementation of role play: Proficient Students Student 1 She is very smart in her age. She seemed interested in English. This was seen when the teacher spoke in English, she could respond with a long answer. She was like a talkative student. She always paid attention to the teacher and kept listening. During the activity, this student was kind of a leader in her group. Since she was the one who was good in English, she led the other members of the group to discuss the topic in the role card. She helped the other students to understand their character, things to do, and what should they say. She also responded to other’s opinion in making the dialog. Besides, she supported her friend’s suggestion in order to make their role play interesting. Student 2 She did not try to answer some of the teacher’s question. She was just listening to the teacher. Although this student had capability in English, she did not take control of her group. She was just like the other members whom they just supported each other to understand the topic. She and her friend in the group helped each other to make the dialog based on the situation given on the card. In addition, she shared some ideas related to the topic. If her advice was out of topic, her friend would tell her to be in line again with the topic. Student 3 She is a clever student. She liked talking to her friends. However, she always tried to answer the teacher’s question. When the teacher addressed a question about the function of narrative, student 3 raised her hand and tried to answer the question. When the teacher asked the same question again to the other students, student 3 still wanted to answer the question. This shows that she kept answering the teacher’s question. Furthermore, during the activity, this student helped other members of the group to practice the role play. She and her friends were trying again and again to demonstrate their role play. Sometimes, in the middle of their practice, they were laughing to each other. It was because their acting was a kind of funny. Student 4 She was little bit quiet. However, she also answered the teacher’s question. When the teacher asked the students to make a sentence using Past Tense, student 4 raised her hand and answered the question. She could make a correct sentence using Past Tense. In the group, she was given a task to write the dialog. Therefore, she just listened to other student’s opinion. She did not contribute any idea toward the topic. However, she helped others practice the dialog Student 5 She showed enthusiasm when the teacher gave some questions. However, she did not raise her hands. She answered the question by grumbling with her friends. Unlike student 4, during the discussion, she responded to other student’s suggestion. Sometimes, she also gave opinion so that their performance would be acceptable. Less Proficient Students Student 6 This student was one of shy students in the class. However, student 6 tried to raise her hand and answered the teacher’s question. During the activity, she inclined to be silent in the group. Still, she could interact with other members of the group. She asked about what she had to do and helped her friend to make the dialog. She was not disruptive during preparing the role play. Although she did not give many ideas, she kept trying to get involved in the activity. Student 7 Student 7 was little bit quite in the class. However, he tried to answer the question by opening the book. He tried to find the answer on the book. During the discussion, student 7 interacted with other students. He worked together with his friend in making the dialog. He contributed an idea so that the role play would be attractive and funny. He was the one in the group who were creative. He made such a joke in the role play. Student 8 She answered the first question that was given by the teacher in early hour. The teacher asked about what narrative text is. Student 8 directly raised her hand and answered the question by looking at the book. This showed that student 8 was eager to participate in the lesson. In addition, she shared some ideas with her friend during the role play. She gave opinion toward the story. She was also helped by other member of how to do with the role card, how she should be, and what should she say. She always tried to practice their part with her friend. d. Student 9 She did not try to answer the teacher’s question. However, she was not disruptive. She still paid attention to the teacher explanation and kept listening to the other students who tried to answer the question. During the role play, she helped each other to make a good ending of the story. She also worked in a team and tried to correct her friend’s mistakes. She was also active in the group during the discussion. e. Student 10 Student 10 was pointed by the teacher. He tried to answer the question with the help of his seatmate. When the teacher asked him about the example of narrative text, he asked his friend. After that he answered the question. During preparation of the role play, student 10 gave his opinion and shared what he knew about the topic. He also supported his friend’s advice. Although he was not pretty good in English, he was not afraid to deliver his idea. He really worked together with his friends in order to make the dialog. Result of the Interview The interview was given to the students in order to know their feeling and opinion about taking part in role playing. The researcher only interviewed the ten selected students. The researcher provided five indicators in the interview. They are: The student’s feelings about taking part in role playing during the teaching and learning process. The student’s opinion about the change (different atmosphere) they had after taking part in role playing. The student’s opinion about the difference between role play and last activity in speaking class. The student’s opinion about the role play. The student’s feeling about the changes they had for their speaking ability. Concerning the data, for the first indicator, all of the students said that they were happy in taking part in the role play activity. 8 out of 10 students felt happy because they could play a “role” and act like the character on the card. Therefore, the students were laughing whenever their friend performed the role play. Others said that it was because a role play was shorter than a drama. They believed that a role play could stimulate them to think faster since they were given 30 minutes to prepare the role play. For the second indicator, 7 students admitted that there was the change (a different atmosphere) they had after taking part in role playing. 3 of them said that they got closer to their friend since the member of each group was chosen by the teacher. They believed that taking part in role playing could strengthen the relationship among friends. 2 of them said that they could think faster because role play stimulates them to do so. Furthermore, 1 of them said that they finally could learn about the character that they played. The last but not the least, 1 student said that she could know the difference between role play and drama. For the third indicator, 5 students said that the difference between a role play and the previous activity was about the time. Role play took a short time for the preparation. It was about 30 minutes while the last activity (drama) took a week to prepare everything. They believed that if they were given a short time to prepare, it would stimulate their brain to think faster. They also said that a role play was more manageable since they could directly perform the role play in a short time. 2 students said that role play simpler than drama since it did not need many properties like costume, light, and make up. 2 students said that role play helped them reduce their anxiety because they could laugh with their friends. However, 1 of the ten students preferred the last activity (drama) because since they were given a week to prepare, meaning that they felt more ready to have the performance. For the fourth indicator, all of the students said some good things about role play. First of all, role play was not complicated. It did not take a long time to prepare. The topic was easy to understand. Besides, each student got the role in random so that they had the same chance to explore their ability. Second, the students could work together to share some ideas with friends through role play activity. Therefore, it strengthened the relationship among friends. Third, role play was fun because it was such a refreshing activity. Fourth, role play stimulated the students to create imagination. The last is role play was a challenging activity because the characters and the topic were chosen by the teacher at the beginning of the meeting. For the last indicator, each of the students answered the question differently. Some said that role play effected their speaking ability and some said it was just usual, no improvement can be made. 2 students said that there were no changes in their speaking ability. 2 students said that they were more confident and not afraid of speaking in front of the class. This is because they thought that role play helped them to practice speaking. Besides, their friends also helped them during the preparation. 5 students said that they knew more about grammar. Therefore, they could speak English more accurately. DISCUSSION The Implementation of Role Play as Speaking Activity Based on the result above, all students were attracted to the role play. As stated by Ladousse (1987), role play means the students play a part (either their own or somebody else’s) in a specific situation and the role is taken on in a safe environment in which students are as inventive and playful as possible. Therefore, the students were enthusiastic about the activity since they were asked to play a role based on the situation written on the card. Besides, they never had such an activity before. In consequence, although they kept questioning about the role play, they showed their willingness towards the role play. Furthermore, role play as, an activity that promotes speaking, gave some advantages during the teaching and learning process. As explained by Ladousse (1987), role play can train the students in speaking skill in any situation. Since the students were asked to pretend to be someone else in a specific situation, they automatically learnt how to use or say the right expression in the right place and at the right time. Another benefit was that role play is a fun activity. The ten selected students agreed about this. They believed that role play was fun because they were acting to be someone else. Therefore, when one of the groups had to perform the role play, the class was all laughing. It was funny to see their friend acting as a robber or police. They played a role that they never play in real life. In addition, role play helped more in building students’ confidence. The proficient students helped shy students to reduce their anxiety when it came to speaking. The interaction created among the students was really helpful because those shy students could rehearse in a safe environment where there was just their friend. Consequently, this also can strengthen the relationship among the students since they helped each other. Finally, since role play demand students to act like different people, they do not feel afraid of committing mistakes. They do not worry if their grammar is incorrect or their pronunciation is wrong. This is because they are asked to be someone else. This makes them feeling free to express anything. Thus, they concentrate more on the fluency aspect. The Student’s Engagement in the Implementation of Role Play From the result of the observation in the previous part, it can be seen that both proficient and less proficient students were engaged in the activity, in this case role play activity. They interacted and shared what they knew during the discussion. Besides, they were given a task to perform the role play in front of the class. This shows that the activity led the students to work in a team. Furthermore, both proficient and less proficient students who were engaged in the activity exhibited three characteristics as stated by Schlechty (1994). Firstly, they are attracted to their work. Since the students never had a role play before, they were curious about the activity. Besides, they were interested in a part written on the role card. They found it fun to act to be someone else. Second, they persist in their work despite challenges and obstacles. Although role play was something new for the students, they kept doing their work. They helped each other in a group if there was something they did not know. The last, they take visible delight in accomplishing their work. This could be seen when they were preparing role play. They enjoyed the learning by laughing within the group. Referring to the engagement theory, the activity and materials in this study contained the three principles mentioned, namely collaboration, project-oriented learning, and authentic focus. Firstly, role play is an activity where the students worked in a group of 4. This is in line with the first principle, collaboration emphasizes team effort that involves communication, planning, management and social skill. Through role play, the students communicate with other students, planned to have a good performance, and unconsciously developed interaction with other students in the group. As stated before in the result of the interview, the students admitted that the relationship among friends was stronger since they worked together during the role play. Second, role play is also a kind of project-oriented learning. The students were given a project where they had to perform the role play in front of the class. They were given a role card but they had to make their own dialogue. By doing so, it stimulated the students to be creative since they were given a chance to make their own ending. Besides, the students could develop their imagination but still this role play was a purposeful activity. Finally, the role play activity had an authentic focus. In engagement theory, authentic focus means doing projects with a realistic focus. As this material was narrative, the teacher gave different materials. She gave a realistic story and characters which mean the role that the students played was not about beautiful princess or handsome prince. It was all about something that might happen to the students. Being a teller of a Bank, policeman, or eyewitness are the examples of a character that they may have in the future. Therefore, the students could learn how to be someone like them and what to say if they were in that position. CONCLUSIONS AND SUGGESTIONS Conclusions Based on the discussion in the previous chapter, it can be concluded that Role playing as speaking activity was beneficial for some reasons. Firstly, it could give the students practicing speaking skill in any situation. As they played a role in a certain circumstance, they learnt how to use some phrases in the right place and time. Second, role play was a fun activity since each student acted to be someone else. It was such a challenge for them to behave like a robber or a policeman. Next, role play built students’ confidence. Since the students rehearsed with their friends whom they usually met, each of whom within a group would help each other to reduce anxiety. Finally, role play was a spontaneous talk which led the students to focus more on the fluency aspect. As they were asked to pretend to be somebody else, they were not afraid of making mistakes. Therefore, they paid attention more on using English in a smooth way. Furthermore, in the implementation of role play, both proficient and less proficient students were engaged in the activity. They actively got involved during the teaching and learning process. Since they were given a project to perform a role play, they created an interaction among the members of the group during the discussion. Besides, they planned to have a good performance and divided a job desk. This showed that they worked cooperatively in a team. In addition, based on the result of the interview, the students believed that role play was an acceptable activity in stimulating their brain to think faster. As they were given a short time to prepare the role play, they had to manage the time for making the dialogue and having rehearsal in a group. Therefore, they had to carefully organize it in order to make a good performance. Suggestions After doing the observation and analyzing the data, the writer would like to give some suggestions. First of all, the topic of the role play should be different from one group to another. This aims to avoid the boredom during the performances. The students would keep their attention if other groups do not have the same play. Secondly, while one group is presenting the role play in front of the class, the teacher should arrange the class in a way that all students can pay attention on their friend performance and are not busy with their own business. Finally, for other researchers who are interested in investigating students’ engagement, it is recommended that they look further on the other related aspects of this study. REFERENCES Huang, I. Y. (2008). Role Play for ESL/EFL Children in the English Classroom. The Internet TESL Journal , XIV (2). Jianing, X. (2007). Storytelling in the EFL Speaking Classroom. The Internet TESL Journal , XIII (11). Kearsley, G & Shneiderman,B. (1999). Engagement Theory: A Framework for Technology-Based Learning and Teaching. Originally at http://home.sprynet.com. Retrieved 13 February 2014 from google ache. Ladousse, G. P. (1987). Role Play: Resource Books for Teachers. Oxford: Oxford University Press. Maznevski, M. L. (1996). Grading Class Participation . Teaching Resource Center . Schlechty, P. (2000). Shaking up the Schoolhouse: How to Support and Sustain Educational Innovation. Jossey Bass Education.